PENDERMAAN SPERMA MENURUT PERSPEKTIF ISLAM - Ismail, Siti Zubaidah (Jurnal Syariah, 2019)
This article follows the case of Diane Blood in Britain who wished to conceive a child using her deceased husband's sperm which had been taken out prior to his death. Several issues are raised by the writer including that of sperm donation from the Islamic perspective. The writer concludes that scientific methods used to conceive are permissible provided that the sperm is materially of a legitimate husband.